Objective assessment of mastication predominance in healthy dentate subjects and patients with unilateral posterior missing teeth. (28th April 2016) - Yamasaki, Y.; Kuwatsuru, R.; Tsukiyama, Y.; Oki, K.; Koyano, K.
Summary: We aimed to investigate mastication predominance in healthy dentate individuals and patients with unilateral posterior missing teeth using objective and subjective methods. The sample comprised 50 healthy dentate individuals (healthy dentate group) and 30 patients with unilateral posterior missing teeth (partially edentulous group). Subjects were asked to freely chew three kinds of test foods (peanuts, beef jerky and chewing gum). Electromyographic activity of the bilateral masseter muscles was recorded. The chewing side (right side or left side) was judged by the level of root mean square electromyographic amplitude. Mastication predominance was then objectively assessed using the mastication predominant score and the mastication predominant index. Self‐awareness of mastication predominance was evaluated using a modified visual analogue scale. Mastication predominance scores of the healthy dentate and partially edentulous groups for each test food were analysed. There was a significant difference in the distribution of the mastication predominant index between the two groups ( P < 0·05). The mastication predominant score was weakly correlated with self‐awareness of mastication predominance in the healthy dentate group, whereas strong correlation was observed in the partially edentulous group ( P < 0·05). The results suggest that the individuals with missing unilateral posterior teeth exhibited greater mastication predominance and were more aware of mastication predominance than healthy dentate individuals. Our findings suggest that an objective evaluation of mastication predominance is more precise than a subjective method.